Mathematics
Answer
Let first term be a and common difference be d of A.P.
By formula,
⇒ an = a + (n - 1)d
5th term = 16
⇒ a5 = 16
⇒ a + (5 - 1)d = 16
⇒ a + 4d = 16 ………(1)
11th term = 34
⇒ a11 = 34
⇒ a + (11 - 1)d = 34
⇒ a + 10d = 34 ……..(2)
Subtracting equation (1) from (2), we get :
⇒ a + 10d - (a + 4d) = 34 - 16
⇒ a - a + 10d - 4d = 18
⇒ 6d = 18
⇒ d = 3.
Substituting value of d in equation (1), we get :
⇒ a + 4(3) = 16
⇒ a + 12 = 16
⇒ a = 4.
A.P. = a, (a + d), (a + 2d), ……..
= 4, (4 + 3), (4 + 2 × 3), ……..
= 4, 7, 10, …….
Hence, A.P. = 4, 7, 10, …….